Digital Citizenship: A bibliographic Review of the Publications in Scopus from 2017 to 2022 (LACCEI, 2024)
The present study aims to describe quantitative metrics regarding the publications on digital citizenship in Scopus from 2017 to 2022.In this sense, the search was carried out consulting the words "citizenship" and "digital" in the Scopus database. Then, we proceeded to filter the studies according to the open access documents, the years of publication and the subject in the database itself, for its subsequent review of the literature. At the end of the review, the last filter was carried out by exclusion criteria, leaving 25 studies as a final result. With the support of the R language and Bibliometrix, it was highlighted that in 2019 there were 6 publications, being the highest rate of scientific production. Similarly, it was recorded that Spain is the country with the most studies published in relation to digital citizenship. The most frequent keywords in the studies carried out on this subject were: digital citizenship, citizenship, education, digital literacy, politics and the Internet. The resulting metrics show the existence of a small number of studies on the subject in Latin America, so there is a need to increase the number of publications for a greater understanding and in-depth analysis of this subject. In addition, it was found that a thematic niche for future research lies in digital citizenship with regard to politics, democracy, and social behavior. Finally, it was possible to conclude that digital citizenship plays a very important role today, because it implies the development of a critical, ethical and reflective attitude to be able to use responsibly the advantages and risks involved in the use and adaptation of tools of information and communication technologies.